Exploring approaches and solutions for urban safety: a focus on the elderly - Tonia Stiuso (TeMA: Journal of Land Use, Mobility and Environment)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility, and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban planning literature review section presents recent books and journals on selected topics and issues within the global scientific panorama. For the third issue of TeMA magazine, volume 17th, this section provides a comprehensive overview of the challenges and solutions related to creating safe and accessible cities for older people. Various scientific sources and practical resources are used to illustrate effective approaches and innovative strategies. The contribution aims to examine these challenges and proposed solutions in the scientific literature, with a special focus on books, journal articles and reports. In particular, the difficulties related to the walkability of urban spaces will be analysed, with a focus on the perception of safety, not only in terms of the prevention of acts of violence, but also with regard to the safety of the physical conditions of streets and roads, as well as the risks arising from traffic.